PENGARUH MARKETING MIX (PRODUCT, PRICE, PLACE, PROMOTION) TERHADAP LOYALITAS PELANGGAN DI OWL BARBER SHOP CIAMIS - Angga Maulana Yusuf; Hammad Mutawakil Hibatillah (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2019)
The objectives to be achieved in this study are first, to find out how the effect of product, price, location and promotion on customer loyalty at Owl Barber Shop Ciamis partially. Second, how the influence of product, price, location and promotion on customer loyalty at Owl Barber Shop Ciamis simultaneously. Third, to find out which variables are the most dominant influencing customer loyalty at Owl Barber Shop Ciamis. Sampling was done randomly with the number of respondents as many as 30 people. Data collection using observation and questionnaires. The data analysis technique used is validity test, reliability test, multicorrelation test, classical assumption test, multiple regression analysis, partial test, simultaneous test, and analysis of the coefficient of determination. The results of the research show that the t-count value of the product variable (2.168) > t-count (2.059) so that Ho is rejected and H1 is accepted, the price variable (27.735) > (2.059) so Ho is rejected and H2 is accepted. While t-count location variable (0.744) < t-table (2.059) so that Ho is accepted and H3 is rejected, and promotion variable (1.619) < t-table (2.059) so Ho is accepted and H4 is rejected. This means that the product and price variables partially affect customer loyalty while the location and promotion variables partially have no effect on customer loyalty. The most dominant variable influencing customer loyalty is the price variable with the t-count value (27.735) greater than the t-count value of product variable (2.168), location (0.744) and promotion variable (1.619).